2020
DOI: 10.3390/sym12101714
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Diversity of Oxabicyclo[2.2.2]octenes Formed between Substituted 2H-Pyran-2-ones and Vinyl-Moiety-Containing Dienophiles

Abstract: In Diels–Alder reactions, 2H-pyran-2-ones as dienes can yield a large variety of cycloadducts with up to four contiguous carbon stereogenic centers. Some of the potentially most useful, however difficult to prepare due to their low thermal stability, are the primary CO2-containing oxabicyclo[2.2.2]octenes, which could be formed as eight distinctive isomers (two sets of regioisomers, each of these composed of four different stereoisomers). A high-pressure synthesis of such products was recently described in a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Our previous extensive experience with bicyclo[2.2.2]octene skeletons [ 28 , 29 , 30 ] has shown that they can provide a very robust and chemically inert nonpeptide skeleton appropriate for further derivatizations. Bicyclo[2.2.2]octenes with fused succinic anhydride rings (i.e., ethenopyrrolo[3,4- f ]isoindoles) can be thus used as starting compounds for transformations with variously substituted primary amines or hydrazine and its derivatives (having one NH 2 group unsubstituted); additionally, they are nowadays quite common fragments of various polymeric materials [ 31 ] and zeolites [ 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous extensive experience with bicyclo[2.2.2]octene skeletons [ 28 , 29 , 30 ] has shown that they can provide a very robust and chemically inert nonpeptide skeleton appropriate for further derivatizations. Bicyclo[2.2.2]octenes with fused succinic anhydride rings (i.e., ethenopyrrolo[3,4- f ]isoindoles) can be thus used as starting compounds for transformations with variously substituted primary amines or hydrazine and its derivatives (having one NH 2 group unsubstituted); additionally, they are nowadays quite common fragments of various polymeric materials [ 31 ] and zeolites [ 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to our extensive research in the field of the preparation of variously substituted bicyclo[2.2.2]octenes via Diels–Alder reactions of 2 H -pyran-2-ones [ 28 , 29 , 30 ], we based the synthesis of the required derivatives 11 on a [4+2] cycloaddition of maleic anhydride with substituted 2 H -pyran-2-ones. According to the retrosynthetic analysis ( Scheme 1 ), we envisaged the following strategy to access the required adducts 11a – o : (i) the first retrosynthetic step includes the application of three regioisomeric pyridylcarbohydrazides 10a – c to derivatize the appropriate bicyclo[2.2.2]octenes 9a – f ; (ii) these are, in turn, formed in the second retrosynthetic step by a double one-pot Diels–Alder cycloaddition between maleic anhydride ( 6 ) and 3-benzoylamino-2 H -pyran-2-one derivatives 5a – f ; (iii) 5 are obtained in the last retrosynthetic step from an appropriately activated carbonyl-group-containing compounds 1a – e , C 1 synthon 2a , b and hippuric acid ( 4 ).…”
Section: Resultsmentioning
confidence: 99%